Barriers to COVID-19 vaccination among medical students in Kazakhstan: development, validation, and use of a new COVID-19 Vaccine Hesitancy Scale - Aidos K. Bolatov; Telman Z. Seisembekov; Altynay Zh. Askarova; Dainius Pavalkis (Human Vaccines & Immunotherapeutics, 2021)
The purpose of this study was to identify the main barriers to vaccine acceptance among medical students in Kazakhstan and to develop the COVID-19 Vaccine Hesitancy Scale (COV-VHS). A cross-sectional study was carried out among students at Astana Medical University (N = 888, Kazakhstan) in March 2021. Only 2% of the participants were currently vaccinated, and 22.4% showed the potential for COVID-19 vaccine acceptance. The following barriers were the most important in COVID-19 vaccine acceptance: concern about possible side effects of vaccination (73%), absence of sufficient evidence on the effectiveness and safety (57%) and quality (42%), the belief that the immune system will cope with COVID-19 even without vaccination (38%), and lack of trust in the effectiveness of vaccination against COVID-19 (33%). Moreover, this study identified the following factors associated with COVID-19 vaccine acceptance: contextual influences (e.g., communication and media environment, socio-demographic factors, vaccination policies, and perception of the pharmaceutical industry), individual and group influences (e.g., personal experience with vaccination, attitudes about health and prevention, trust in the health system and providers, perceived risk), and specific issues on COVID-19 vaccine/vaccination (e.g., choice of vaccine can reduce vaccine hesitancy by 30%). A developed 12-item 6-factor model of COV-VHS showed good validity and reliability. In conclusion, there was a low-level potential for COVID-19 vaccine acceptance among medical students in Kazakhstan. Thus, an effective vaccination education and policy are needed to combat the COVID-19 pandemic.